/
/
/
A projectile is thrown upward so that its distance above the ground
Not my Question
Flag Content

# Question : A projectile is thrown upward so that its distance above the ground : 2163529

MULTIPLE CHOICE. Choose the one alternative that best completes the statement or answers the question.

Find the vertex of the parabola.

41) A projectile is thrown upward so that its distance above the ground after t seconds is h = -15t2 + 510t. What is its maximum height?

A) 4335 ft

B) 211,395 ft

C) 7425 ft

D) 13,583 ft

42) If an object is thrown upward with an initial velocity of 15 ft per second, its height is given by h = -15t2 + 60t after time t seconds. What is its maximum height?

A) 227 ft

B) 30 ft

C) 225 ft

D) 60 ft

43) The number of mosquitoes M(x), in millions, in a certain area depends on the June rainfall x, in inches: M(x) = 15x - x2. What rainfall produces the maximum number of mosquitoes?

A) 0 in.

B) 225 in.

C) 15 in.

D) 7.5 in.

44) Which of the pairs of numbers whose sum is 86 has the largest product?

A) 33 and 53

B) 39 and 47

C) 43 and 43

D) 42 and 44

45) A banquet manager decides to charge \$80 per person for dinner and \$13 for each person who does not show up. If there are places set for 132 people, and if x represents the number of people who do not show up, write an expression for the total revenue of the banquet.

A) R(x) = (132 + x)(80 + 13x)

B) R(x) = 80(132 - x) + 13x

C) R(x) = 80(132 + x) + 13x

D) R(x) = (132 + x)(80 - 13x)

Graph the equation.

46) f(x) = (1/3)x2

A)

B)

C)

D)

47) f(x) = -2x2

A)

B)

C)

D)

48) f(x) = x2 - 4

A)

B)

C)

D)

49) f(x) = -2x2 + 4

A)

B)

C)

D)

50) f(x) = - (1/4)x2 + 9

A)

B)

C)

D)

51) f(x) = (x + 5)2

A)

B)

C)

D)

52) f(x) = (x - 2)2 + 3

A)

B)

C)

D)

53) f(x) = 4(x + 3)2 - 1

A)

B)

C)

D)

54) f(x) = -2(x - 6)2 + 4

A)

B)

C)

D)

55) f(x) = - (3/5) (x + 5)2 + 3

A)

B)

C)

D)

Identify the vertex of the given parabola.

56) f(x) = (x - 5)2 - 5

A) (-5, 0)

B) (5, -5)

C) (5, 5)

D) (0, -5)

57) f(x) = x2 + 5

A) (-5, 0)

B) (5, 0)

C) (0, -5)

D) (0, 5)

58) f(x) = (x + 5)2 + 9

A) (-9, 5)

B) (9, -25)

C) (-5, 9)

D) (9, -5)

59) f(x) = (x + 5)2 - 3

A) (-5, -3)

B) (-5, 3)

C) (5, 3)

D) (5, -3)

60) f(x) = x2 - 6

A) (6, 0)

B) (0, -6)

C) (1, 0)

D) (0, 6)

## Solution 5 (1 Ratings )

Solved
Algebra 2 Years Ago 226 Views